Diagnostic Accuracy of an MRI Protocol of the Knee Accelerated Through Parallel Imaging in Correlation to Arthroscopy - Schnaiter, Johannes Walter; Roemer, Frank; Mckenna-Kuettner, Axel; Patzak, Hans-Joachim; May, Matthias; Janka, Rolf Matthias; Uder, Michael; Wüst, Wolfgang (Röfo-Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2018)
PURPOSE: Parallel imaging allows for a considerable shortening of examination times. Limited data is available about the diagnostic accuracy of an accelerated knee MRI protocol based on parallel imaging evaluating all knee joint compartments in a large patient population compared to arthroscopy. MATERIALS AND METHODS: 162 consecutive patients with a knee MRI (1.5 T, Siemens Aera) and arthroscopy were included. The total MRI scan time was less than 9 minutes. Meniscus and cartilage injuries, cruciate ligament lesions, loose joint bodies and medial patellar plicae were evaluated. Sensitivity (SE), specificity (SP), positive predictive value (PPV), and negative predictive value (NPV), as well as diagnostic accuracy were determined. RESULTS: For the medial meniscus, the values were: SE 97 %, SP 88 %, PPV 94 %, and NPV 94 %. For the lateral meniscus the values were: SE 77 %, SP 99 %, PPV 98 %, and NPV 89 %. For cartilage injuries the values were: SE 72 %, SP 80 %, PPV 86 %, and NPV 61 %. For the anterior cruciate ligament the values were: SE 90 %, SP 94 %, PPV 77 %, and NPV 98 %, while all values were 100 % for the posterior cruciate ligament. For loose bodies the values were: SE 48 %, SP 96 %, PPV 62 %, and NPV 93 %, and for the medial patellar plicae the values were: SE 57 %, SP 88 %, PPV 18 %, and NPV 98 %. CONCLUSION: A knee MRI examination with parallel imaging and a scan time of less than 9 minutes delivers reliable results with high diagnostic accuracy. KEY POINTS: · An accelerated knee MRI protocol with parallel imaging allows for high diagnostic accuracy.. · Especially meniscal and cruciate ligament injuries are well depicted.. · Cartilage injuries seem to be overestimated.. CITATION FORMAT: · Schnaiter JW, Roemer F, McKenna-Kuettner A et al. Diagnostic Accuracy of an MRI Protocol of the Knee Accelerated Through Parallel Imaging in Correlation to Arthroscopy. Fortschr Röntgenstr 2018; 190: 265 - 272.
EVALuna2:34702